Design, Construction, and Testing of an Electric Wheelchair Operated by Arduino Uno R3 Microcontroller - Subagyo, Yusuf; Sendie Yuliarto Margen; Baharudin Priwintoko; Fariz Wisda Nugraha; Hartanto Prawibowo (Multidisciplinary Innovations and Research in Applied Engineering, 2025)
The research aims to design and develop an electric wheelchair based on the Arduino Uno microcontroller as a mobility solution for individuals with disabilities. A conventional wheelchair was modified by integrating an electric drive system controlled by an analog joystick, which is connected to the Arduino Uno and DC motors via a BTS 760 motor driver. The wheelchair design complies with ISO 7176-5 standards and is adapted to the anthropometric dimensions of Indonesian users. Test results indicate that the control system functions effectively, allowing responsive control of wheelchair movements forward, backward, left, and right according to joystick operation. However, several challenges were encountered during the chain adjustment and gear welding processes, requiring further development to achieve optimal performance. This study demonstrates that utilizing the Arduino Uno as the central control unit enables the production of an electric wheelchair at a more affordable cost.